PEMERIKSAAN ULANG ATAS PEMBATALAN KETETAPAN PAJAK SECARA FORMAL - Suparna Wijaya; Yudhan Wahyu Illahi (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2022)
Directorate General of Taxes has several times faced the fact that the tax assessments that have been issued have been formally canceled. The purpose of this study is to determine the re-audit procedure for tax assessments that are formally canceled, and the obstacles and solutions in overcoming tax audit problems against audit results disputes. The research method used is descriptive qualitative. The results of the study reveal that a tax assessment that is formally canceled can be followed up by a tax auditor, namely in the form of a new audit or a follow-up tax audit. The new tax audit means that the tax audit is carried out with the usual audit mechanism with a different purpose/regardless of the previous tax audit. A new audit is carried out if the cancellation of the tax assessment occurs because it is not true. Advanced audit means to continue the previous process. The obstacles are external and internal factors. External factors include the provision of tax legal remedies, lack of experience, and lack of legal assistance in dealing with disputes over audit results. Internal factors in the form of disciplinary punishment to tax employees who fail to carry out their duties. The solution can be done in terms of regulation and the effectiveness of tax audits.